Behavior of Normal Concrete Reinforced with Fiber - Prabowo Setiyawan (JACEE (Journal of Advanced Civil and Environmental Engineering), 2021)
Concrete is a material with the ability to withstand a fairly high pressure, yet it has a low ability to withstand tension. To be utilized as a structure material, improvements need to be made to increase its tensile strength. Addition of fiber in the concrete mixture is recognized to be one among the existing methods to increase the tensile strength. Considering its high tensile strength, This study aimed to examine the compressive strength, the split tensile strength, the flexural and elastic modulus of the normal concrete with Menjalin fibers. The examination was conducted using a cylinder with the diameter of 15 cm and the height of 30 cm and a beam with the size of 15x15x60 cm. Fiber addition was 0.65% of the total concrete materials with various fiber lengths ranging from 2.5 cm, 5 cm, 7.5 cm to 10 cm. The experiment was made by the means of a concrete cylinder compressive test and a flexural test of unreinforced concrete blocks. Results of the study showed, at the age of 21 days, the highest average compressive strength value of 194.37 kg/cm2 and the split tensile strength of 30.43 kg/cm2 in the concrete with fiber of 5 cm long were obtained. The highest flexural modulus value of concrete occurred in the specimen with the fiber length of 7.5 cm (55.7 kg/cm2), while the highest elasticity of concrete occurred in the specimen with the fiber length of 5 cm (2.45x105 kg/cm2).